2020
DOI: 10.3389/fimmu.2020.02088
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Stromal Lymphopoietin and Cancer: Th2-Dependent and -Independent Mechanisms

Abstract: The thymic stromal lymphopoietin (TSLP) is an IL-7-like cytokine originally cloned from a murine thymic stromal cell line, and subsequently a human homolog was identified using database search methods. Human TSLP is mostly expressed in epithelial cells, among which are keratinocytes as well as stromal cells such as fibroblasts and immune cells. Human TSLP was first described to activate myeloid dendritic cells, which prime naïve T helper cells to produce high concentrations of Th2 cytokines, thus representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 67 publications
2
24
0
Order By: Relevance
“…The interaction between a non-IgE-mediated stimulus, such as LPS, T H 2 cytokines and TSLP in human lung macrophages greatly extend the potential proinflammatory roles of TSLP in inflammatory lung disorders. The relevance of TSLP-dependent T H 2 inflammation in allergic disorders and in cancer has been recently emphasized [2,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between a non-IgE-mediated stimulus, such as LPS, T H 2 cytokines and TSLP in human lung macrophages greatly extend the potential proinflammatory roles of TSLP in inflammatory lung disorders. The relevance of TSLP-dependent T H 2 inflammation in allergic disorders and in cancer has been recently emphasized [2,28].…”
Section: Discussionmentioning
confidence: 99%
“…The plethora of immune cell types that can either produce or respond to TSLP emphasizes the importance of this cytokine in multiple biological processes [1,2]. A novel and unexpected function of TSLP has been demonstrated in experimental and human cancers [2,28]. In particular, TSLP has been linked to the progression of several experimental [29][30][31][32][33] and human tumors [33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest possible mechanisms by which IER5 regulates the infiltration of Th2 cells, along with γδ T cells in glioma patients. Th2 cytokines such as IL-4, IL-10, IL-5, IL-9, and IL-6 can down-regulate tumor-specific immunity (Protti and De Monte, 2020). These cytokines along with their receptors were highly expressed in glioblastoma samples and cell lines (Hao et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that Th2 and mast cells were significantly infiltrated in gastric cancer patients. Strong infiltration by Th2 cells may be associated with early carcinogenesis and promote the activation of a tumor microenvironment that favors angiogenesis and metastasis [ 33 ]. Studies have shown that Th2 cell responses are associated with the development and progression of human gastric cancer [ 34 ].…”
Section: Discussionmentioning
confidence: 99%